Enhancing SME Business Savings through HR Practices and Financial Literacy - Sumastuti, Efriyani Sumastuti (Ilomata International Journal of Management, 2024)
This study explores how human resource (HR) practices influence business savings in small and medium enterprises (SMEs) through the mediation of financial literacy and savings motives. The primary objective is to determine the extent to which HR practices enhance business savings by improving employees' financial literacy and motivating savings behavior. Addressing the gap in integrating HR strategies with financial education, this research employs a quantitative approach using structural equation modeling (SEM) via Smart PLS 3. Data were collected from 241 SME employees through structured questionnaires. The results indicate that HR practices significantly boost business savings, primarily by enhancing financial literacy among employees. Although HR practices positively impact savings motives, these motives alone do not significantly mediate the relationship with business savings. The study concludes that incorporating financial literacy into HR practices is essential for fostering better financial decision-making and achieving substantial business savings. Consequently, SMEs should prioritize financial education within their HR strategies to improve their financial outcomes.